2019
DOI: 10.35663/amp.2018.353.510
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico, clínico-psiquiátrico y legal del sentenciado por delitos sexuales, Establecimiento Penitenciario Lurigancho, Lima, 2017

Abstract: Objetivo: Determinar el perfil epidemiológico, clínico-psiquiátrico y legal del interno recluido por delitos sexuales, Establecimiento Penitenciario Lurigancho –de varones–, Lima, 2017. Materiales y métodos: Estudio con diseño observacional, descriptivo, transversal y retrospectivo. La muestra estuvo compuesta por la totalidad de los informes para los trámites del beneficio penitenciario de redención de pena de los internos sentenciados por algún delito sexual que pasaron por la evaluación psiquiátrica en el a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…The socio-demographic results obtained enabled us to identify a characteristic profile of the patients with diminished responsibility in the sample: male, middle aged, from the capital or mountain regions, different number of years in secondary education, unemployed or working in jobs where specialised academic training is not required, without a partner or children. This profile matches other Peruvian 16 , 17 , 24 , Latin American 6 , 25 , European 26 , 27 and African studies 28 . On the other hand, a study in the USA found an average age of 42.2 years; older than the ages found in this study, although the American study only included persons with diminished responsibility sentenced for sexual crimes.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The socio-demographic results obtained enabled us to identify a characteristic profile of the patients with diminished responsibility in the sample: male, middle aged, from the capital or mountain regions, different number of years in secondary education, unemployed or working in jobs where specialised academic training is not required, without a partner or children. This profile matches other Peruvian 16 , 17 , 24 , Latin American 6 , 25 , European 26 , 27 and African studies 28 . On the other hand, a study in the USA found an average age of 42.2 years; older than the ages found in this study, although the American study only included persons with diminished responsibility sentenced for sexual crimes.…”
Section: Discussionsupporting
confidence: 84%
“…El presente estudio es el primero en el Perú que cuantifica a las personas inimputables por trastornos mentales que pasaron por el sistema penitenciario a nivel nacional, y describe sus características epidemio- Los resultados sociodemográficos obtenidos permitieron identificar un perfil característico de los pacientes inimputables en la muestra estudiada: de sexo masculino, mediana edad, procedente de la capital o de la sierra, con diferentes años de secundaria concluidos, desempleado o con trabajos sin formación académica especializada, sin pareja e hijos. Este perfil concuerda con otros estudios peruanos 16,17,24 , latinoamericanos 6,25 , europeos 26,27 y africanos 28 . Por otro lado, el estudio realizado en los Estados Unidos encontró una edad media de 42,2 años, mayor que en el presente estudio, aunque solamente se consideraron los inimputables por delitos sexuales.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This specific construct is configured within PDs and appears to be an important predictor of subsequent violence, crime, and recidivism (Hengartner et al, 2018). In the national context, although research is limited, it was found that 17.1% of convicted sex offenders at the Lurigancho Penitentiary have a mental disorder, including PD (Sindeev & Guzmán-Negrón, 2019), while more than 50% of the inmates of the Arequipa Penitentiary show psychopathic deviation and 38.4%, antisocial disorder (Arias et al, 2016;Arosquipa & Gutiérrez, 2016). Moreover, at the local level, antisocial disorder (55.8%) and narcissism (51.2%) are the most prevalent PD diagnoses among the inmates of the DeVida program at the HP (Gomez, 2018).…”
Section: The Need For a Comprehensive Measure Of Icd-11 Pd In Correct...mentioning
confidence: 99%